1978
DOI: 10.1002/1097-0142(197804)41:4<1217::aid-cncr2820410401>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of a choriogonadotropin-like protein in bacteria isolated from cancer patients

Abstract: By the use of specific antibody to human chorionic gonadotropin (CG) as well as to its β‐subunit, and the application of the indirect fluorescein‐labeled and peroxidase‐labeled antibody techniques, we have demonstrated the presence of a membrane (wall)‐associated CG‐similar immunoreactive protein in 15 strains of bacteria isolated from tissues of patients bearing malignant neoplasms. These microorganisms were classified as S. epidermidis, (12), E. coli (2), and a single strain of P. maltophilia (ATCC 13637). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…For TEM studies, all bacteria (hCG-producers and controls) were grown aerobically in Trypticase soy broth at 35 "C for 18 h and subsequently fixed for a minimum of 2 h with cold (4 "C) 3% (w/v) glutaraldehyde in 0.1 M-phosphate buffer pH 7.4 containing 1 % (w/v) CaC12. Subsequent preparation of the specimens was as described by Acevedo et al (1981 h).…”
Section: Bacterial Culturessupporting
confidence: 58%
See 1 more Smart Citation
“…For TEM studies, all bacteria (hCG-producers and controls) were grown aerobically in Trypticase soy broth at 35 "C for 18 h and subsequently fixed for a minimum of 2 h with cold (4 "C) 3% (w/v) glutaraldehyde in 0.1 M-phosphate buffer pH 7.4 containing 1 % (w/v) CaC12. Subsequent preparation of the specimens was as described by Acevedo et al (1981 h).…”
Section: Bacterial Culturessupporting
confidence: 58%
“…Most of those isolates were from cancer patients (Livingston & Alexander-Jackson, 1970;Cohen & Strampp, 1976;Acevedo et al, 1978Acevedo et al, , 1979Acevedo et al, , 1981Maruo et al, 1979;Backus & Affronti 1981 ;Domingue et al, 1986). These findings have important biological implications (Domingue et al, 1986) because (1) they constituted the first demonstration of the natural synthesis by prokaryotes of a biologically active material Abbreviations: hCG, human choriogonadotropin ; CWD, cell wall deficient; MoAb, monoclonal antibody; TEM, transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Livingston and Livingston (50), Cohen and Strampp (51), and Acevedo et al (52) have demonstrated that a human choriogonadotropin-like material is produced by bacteria, and our studies suggest § (53) that it is extractable from fish. LeRoith et al (53) have shown that bioactive ACTH and immunoactive A-endorphin were extractable from protozoa.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, Acevedo et al (22), using immunocytochemical techniques, reported that CG-like protein is present in several microorganisms that were isolated from patients bearing malignant neoplasms. However, these findings should be substantiated by other methods in view of the fact that subunits of glycoprotein hormones and serine proteases possess a homologous peptide sequence (23).…”
Section: Resultsmentioning
confidence: 99%